Chemical Modeling of Zinc Enzymes - DeLaBarre, Byron (My University, 1995)
This work describes efforts towards creating chemical models for a variety of zinc based metalloenzymes. A background on the current progress of modeling zinc enzymes is presented, as is a brief review of zinc biochemistry. The structure of triaquo(tris-2-pyridylphosphine)nickel(ll) dinitrate is presented and compared with its zinc analogue. Both structures have octahedral geometry with no unusual bond lengths. The synthesis and characterization of bis(2,4,5-tribromoimidazole)(diaquo)zinc(II). (II) is also presented in this work. A similar compound, Zn(Im)2 (III) was also prepared in this work. Both compounds were characterized by X-ray crystallography, IR spectroscopy, and elemental analysis. Neutron crystallography was used to characterize (II) as a peraquo species. Both (II) and (III) possess tetrahedral geometry about the zinc atom. (III) is multiply catenated and cannot be considered as a discrete molecular species. The pKa2 of 2,4,5-tribromoimidazole, the organic ligand in (II), was measured and found to be 10.7(2). Bond valence theory was used to analyze (II). Extended Huckel molecular orbital calculations were carried out on (II). (II) was compared with a variety of other zincimidazole compounds. It was discovered that (II) has unusually small carbon-nitrogen-carbon angles within its tribromoimidazole rings. It is uncertain whether this feature is because of the coordination of the tribromoimidazole rings to the zinc atom, or whether it is an inherent feature of the tribromoimidazole rings. A copper analogue of (II) has also been synthesized and has been tentatively assigned the formula Cu(lmBr3)2(OH2)2 . X-ray characterization of this compound has not yet been accomplished.
This thesis is missing pages 9, 39, 108-110. The pages are not in the other copies of the thesis. -Digitization Centre
Keywords: chemical modeling; zinc; zinc enzymes; enzyme